The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.4103/abr.abr_344_21
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the relationship between pregnancy-associated plasma protein A (PAPP-A) and pregnancy outcomes

Abstract: Background: In the current study, we aimed to evaluate the association between pregnancy-related plasma protein-A (PAPP-A) levels measured in the first trimester and pregnancy outcomes. Materials and Methods: This is a descriptive-analytical study that was performed in 2019--2021 on 1061 pregnant women in their first trimester. Demographic and basic information of all women were collected. These data included age, weight, parity, and date of delivery. Then the quantity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Based on these studies, PAPP-A seems to be a valid marker in predicting adverse pregnancy outcomes. Recently, a study confirmed these results, demonstrating that low PAPP-A levels in the first trimester of pregnancy are associated with a higher risk of having poor pregnancy outcomes, such as a preterm delivery and PE [36]. In contrast, elevated PAPP-A levels in the first trimester of pregnancy have been associated with a higher risk of developing placenta accreta spectrum disorders (PASs).…”
Section: Papp-a (Pregnancy-associated Plasma Protein-a)mentioning
confidence: 87%
See 1 more Smart Citation
“…Based on these studies, PAPP-A seems to be a valid marker in predicting adverse pregnancy outcomes. Recently, a study confirmed these results, demonstrating that low PAPP-A levels in the first trimester of pregnancy are associated with a higher risk of having poor pregnancy outcomes, such as a preterm delivery and PE [36]. In contrast, elevated PAPP-A levels in the first trimester of pregnancy have been associated with a higher risk of developing placenta accreta spectrum disorders (PASs).…”
Section: Papp-a (Pregnancy-associated Plasma Protein-a)mentioning
confidence: 87%
“…PAPP-A levels increase during pregnancy, with higher concentration at term and a rapid reduction after delivery [ 34 ]. Several studies demonstrated that lower levels of PAPP-A detected during the first trimester screening were associated with a higher risk of complicated pregnancy (PE, IUGR, preterm birth) [ 35 , 36 ]. For instance, a PAPP-A of less than 0.4 multiple of the median (MoM) is predictive of third-trimester complications, such as preeclampsia, IUGR or preterm birth [ 37 ].…”
Section: Protein Placental Biomarkersmentioning
confidence: 99%